Tutorial: Internet of Things and the upcoming wireless sensor networks related with the use of big data in mapping services; issues of smart cities - Gonzalez Jaramillo, V. (2016)
Some years ago we used to talk about a very far future, a dream in where people can access to services and information into small devices; in which we can accesses to information, make calls, watch videos and surf maps. That far future is not so far, actually the advance of technology involves a more powerful hardware which is day to day is becoming into small devices with big resources [14]. The upcoming development of electronic allows that these devices could be integrated into smart networks [8]; these networks are called Wireless Sensor Networks (WSN; [13]). WSN do not need physical connections, they use communication systems such as ZigBEE, WiFi, Bluetooth, GSM [7]. Each individual device called moth have autonomous characteristics of communications, storage of data, automatic organization and recovery of the network communication among others that allow the network performs an autonomous work, with the possibility of Internet connection. These characteristic let emerge the so called Internet of Things (IoT), phrase that was coined in the early 1990's, where everyday objects have network connectivity, allowing them to send and receive data [1]. Since these days, technology has an exponential advance and now it is possible to find devices that permit earth observations in real time [11,15,4]. All this collected information use cloud and no-cloud storage [3]. These systems allow to store big amounts of data [6], that is collected from devices integrated in the concept of IoT [5] (especially incomes from smartphones, GPS's devices and various earth observation sensors). The analysis of this big data (some of them spatial information) will be helpful in treatment and finding related solutions in specific areas such as public administration, environment, urban services, etc. [12]. Also, the data that at the beginning was depicted like sparse information, it begins to converge into a shape. This shape can be seen like maps that could be paper maps or digital ones- The representation of the information into maps is linked to a wide range of disciplines and the concept is not new but the enhancement that it has reached until now is incredible, especially the digital information given in Internet which could be accessed by electronic devices (smart phones, tablets and computers). E-government services would improve efficiency and consequently citizen's satisfaction due to the implementation of Spatial Data Infrastructure (SDI, [9]). In order to good development of SDI, the Open Geospatial Consortium (OCG) has an important role. OGC is an international industry consortium of companies, government agencies and universities participating in a consensus process to develop publicly available interface standards [10]. One of the most popular OGC standards is the Web Map Service (WMS) that allows to show spatial information, considered fundamental for the development of many of the services in the way that a citizen can access to e-government services (e.g., cadastre, [2]) and e-democracy. In this talk, the objective is to introduce some concepts considered essential in the development of the modern society and smart cities. Concepts such as IoT, big data and mapping not only allow the collection or merely visualization of information; these promote the enhancement of access to e-services, also they could be used to face challenges that a good administration of the limited resources implies.